Tanna Times Islanders in the World - Lindstrom, Lamont (University of Hawai'i Press, 2020)
"Anthropologists like to tell other people's stories but local experts tell them even better. This book introduces the vibrant living culture and fascinating history of Tanna, an island in Vanuatu, Melanesia, through the stories of a dozen interconnected Tanna Islanders. Tracing the past 250 years of island experiences that cross the globe, each of these distinctly extraordinary lives tells larger human narratives of cultural continuity and change. In following Tanna's times, we find that all of us, even those living on seemingly out-of-the-way Pacific Islands, are firmly linked into the world's networks. Each chapter opens with a telling life story then contextualizes that biography with pertinent ethnographic explanation and archival research. Since 1774, Tanna Islanders have participated in events that have captured global anthropological and popular attention. These include receiving British explorer James Cook; a nineteenth-century voyage to London; troubled relations with early Christian missionaries; overseas emigration for plantation labor; the innovation of the John Frum Movement, a so-called Melanesian "cargo cult"; service in American military labor corps during the Pacific War; agitation in the 1970s for an independent Vanuatu; urban migration to seek work in Port Vila (Vanuatu's capital); the international kava business; juggling arranged versus love marriages; and modern dealings with social media and swelling numbers of tourists. Yet, partly as a consequence of their experience abroad, Islanders fiercely protect their cultural identity and continue to maintain resilient bonds with their Tanna homes. Drawing on forty years of fieldwork in Vanuatu, author Lamont Lindstrom offers rich insights into the culture of Tanna. His close relationship with the island's people is reflected in his choice to feature their voices; he celebrates and recounts their stories here in accessible, engaging prose. An ethnographic case study written for students of anthropology, the author has included a concise list of key sources and essential further readings suggestions at the end of each chapter. Tanna Times complements classroom and scholarly interests in kinship and marriage, economics, politics, religion, history, linguistics, gender and personhood, and social transformation in Melanesia and beyond."